1996
DOI: 10.1038/bjc.1996.226
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of [131I]MIBG in nude mice bearing SK-N-SH human neuroblastoma xenografts: effect of specific activity

Abstract: Summary The biodistribution of no-carrier-added (n.c.a) meta-[131I]iodobenzylguanidine ([131I]MIBG) and that prepared by the standard isotopic exchange method were compared in athymic mice bearing SK-N-SH human neuroblastoma xenografts. No advantage in tumour uptake was observed for the n.c.a. preparation. BALB/c nu/nu mice exhibited lower uptake in highly innervated normal tissues (heart and adrenals) than normal BALB/c mice. In another experiment, the distribution of n.c.a.[131I]MIBG in the absence or presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…Compared to non-tumor-bearing nude mice, the relative excretion of MIBG and metabolites in the other groups of animals did not differ statistically significantly. et al, 1991) and agreed closely with radio-iodinated MIBG studies in comparable neuroblastoma-mouse models (Gaze et al, 1994;Vaidyanathan et al, 1996a). In conventional C 3 H mice (Table II), the radioactivity in tissues known to be the normal MIBG targets in humans (Nakajo et al, 1983), i.e., the heart, spleen, and adrenals, was significantly higher than in nude mice, which is probably related to strain differences in stress sensitivity.…”
Section: [ 131 I]mibg Tissue Distribution Excretion and Tumor Levelssupporting
confidence: 62%
See 2 more Smart Citations
“…Compared to non-tumor-bearing nude mice, the relative excretion of MIBG and metabolites in the other groups of animals did not differ statistically significantly. et al, 1991) and agreed closely with radio-iodinated MIBG studies in comparable neuroblastoma-mouse models (Gaze et al, 1994;Vaidyanathan et al, 1996a). In conventional C 3 H mice (Table II), the radioactivity in tissues known to be the normal MIBG targets in humans (Nakajo et al, 1983), i.e., the heart, spleen, and adrenals, was significantly higher than in nude mice, which is probably related to strain differences in stress sensitivity.…”
Section: [ 131 I]mibg Tissue Distribution Excretion and Tumor Levelssupporting
confidence: 62%
“…administered MIBG were seen between conventional and athymic nude BALB/c mice (Vaidyahathan et al, 1996a). Under comparable conditions of neuroblastoma-bearing animals, C 3 H nu/nu mice exhibited 40% to 70% lower [ 131 I]MIBG levels in heart, spleen, lungs, and liver but about similar levels in the adrenals compared with BALB/c nu/nu mice (Vaidyanathan et al, 1996a;Rutgers et al, 1994). This variation in MIBG biodistribution between nude mice with different genetic Fig.…”
Section: Mibg Handling In Mice and Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…High specific activity 125 I-MIBG appeared to be more cytotoxic than conventional 131 I-MIBG in 500 micron neuroblastoma spheroids [48]. In neuroblastoma xenografts, tumor uptake was enhanced in mice receiving the no-carrier-added formulation compared to conventional 131 I-MIBG [47], although this result was not replicated by a different group [49]. Given the theoretical advantages of this formulation, no-carrier-added 131 I-MIBG has now entered clinical trials in children with neuroblastoma.…”
Section: Preclinical Studies Of Radiolabeled Mibg In Neuroblastomamentioning
confidence: 99%
“…Thus, the low-energy emission of [ 125 I]MIBG will be more fully absorbed in small target volumes with negligible radiation exposure of nontargeted neighboring cells and this radiopharmaceutical has therefore been advocated for treatment of microscopic neuroblastoma [10,[15][16][17]. For this we used the well-characterized, immature human neuroblastoma SK-N-SH [21][22][23][24] and a highly differentiated rat pheochromocytoma PC12 [21,25]. Cunningham et al [16] recently showed that [ 125 I]MIBG was even superior to [ 131 I]MIBG in inhibiting the growth of spheroids of the SK-N-BE(2c) human neuroblastoma.…”
Section: Introductionmentioning
confidence: 99%